EFFECTIVENESS OF THE APPLICATION OF ORGANIC MATTER AND TRICHODERMA VIRIDE FROM SUPPRESIVE SOIL TO CONTROL FUSARIUM WILT ON BANANA PLANT - Ivayani, Ivayani; Ginting, Cipta; Yusnita, Yusnita; Dirmawati, Suskandini Ratih (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2018)
Effectiveness of the application of organic matter and Trichoderma viride from suppresive soil to control fusarium wilt on banana plant. Fusarium wilt disease caused by Fusarium oxysporum f.sp. cubense is one of the problems in banana production. This research was aimed to evaluate the effect of  Trichoderma viride isolated from suppresive soil and organic matter on controlling fusarium wilt on banana plant. The efficcacy trial consisted of 12 treatments and four replications within each treatment. Each experimental unit consisted of 10 plants. Organic matters used were rice straw, cassava peel, and compost. Treatments were arranged in a randomized complete block design. Data obtained were analyzed by analysis of variance followed by orthogonal analysis (P?0.05). Application of T. viride suppressed disease incident up to 65%. The highest disease incident occurred in plants treated without T. viride and organic matter and in plants treated with organic matter only (78.33%). Disease incidence in plants treated with T.viride was lower than those treated with the combination of T. viride and organic matter. Different application times (in nursery or soil medium) did not significantly affect fusarium wilt incidence. The type of organic matter did not significantly affect the incidence and severity of fusarium wilt.